The Relationship between Breastfeeding and Parenting Patterns with Early Childhood Emotional Development - Ermina Syainah; Nurhamidi Nurhamidi; Syahrial Shaddiq (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Children’s mental-emotional development involves the interaction between physiological maturation and the psychological mechanisms that process and control emotions. This study aims to determine the relationship between exclusive breastfeeding and parenting patterns with the mental and emotional development of early childhood in the Guntung Manggis Health Center working area in 2021. This analytical observational study utilized a cross-sectional design. The sample comprised 92 children aged 3 to 6 years, selected through simple random sampling. Data were analyzed using Spearman Rank correlation. The analysis revealed a significant relationship between exclusive breastfeeding, mental-emotional development (ρ = 0.0), parenting patterns, and mental-emotional development (ρ = 0.00). Specifically, exclusive breastfeeding was associated with improved mental-emotional development in 65% of the sample, and positive parenting patterns were linked to enhanced development in 72% of the cases. The findings suggest that exclusive breastfeeding and positive parenting patterns support optimal mental and emotional development in early childhood. It is recommended that mothers provide exclusive breastfeeding and adopt positive parenting strategies to foster better developmental outcomes for their children.